Predictors for Disease Severity in Covid-19 - Rida Gul, Ayesha Gul Ayesha Gul, Rida Gul, Hamza Sattar Khan, Dawood Khan, Muhammad Haroon, Asghar Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronavirus disease 2019 affects millions of people to date. Age, comorbidities, fever, shortness of breath, and different Laboratory parameters like serum forum, C- reactive protein, and lactate dehydrogenase level are the important predictors for the severity of the disease. Material and methods: This case-control type study was conducted in April to June2021 in Khyber Teaching Hospital Peshawar. PCR-detected coronavirus disease 2019 patients were assessed. These patients were divided into four groups based on presenting symptoms, image findings for pneumonia, oxygen saturation, and ventilatory support. These groups were compared for different parameters, including the presenting symptoms and laboratory parameters. Results: Out of 140 patients, 54.3% were males. There was a statistically significant difference (p< 0.05) in presenting complaints like fever, shortness of breath, body aches, loss of taste, anorexia, and laboratory parameters like serum ferritin, total leucocyte count, lactate dehydrogenase, C-reactive proteins, and d-dimers in these groups based on the severity of the disease. These parameters were independent predictors for disease severity in Coronavirus disease 2019. Further studies are recommended with a large sample size for more evaluation of these associations. Practical Implication: This study will be helpful in determing the disease severity prediction in patients suffering from COVID-19. For community benefit, this study will be important as it helps the people to determine either they are sufferimg from COVID-19 or not. It will also help them to take the necessary precautionary measures. Conclusion: The study concluded that there are several clinical predictors of COVID -19 like fever, old age anorexia, loss of taste, shortness of breath, and muscle aches. In addition, some laboratory markers such as serum ferritin, CRP level, total leucocyte count, and LDH are responsible for indicating the disease severity. Earlier disease prediction results in timely and early intervention, thereby helps in the prevention of progression toward critical stage. Keywords: Coronavirus disease 2019 (COVID-19), disease severity, mild and moderate disease, severe and critical disease